Construção e validação de mapa estratégico com ênfase na dimensão da aprendizagem e crescimento: estudo de caso em uma unidade de uma Instituição de Ensino Superior - Sponchiado, Paulo José (Universidade do Vale do Rio do Sinos, 2006)
This paper proposes the construction and validation of a Strategic Map (SM), with emphasis in the perspective of learning and growing, applicable to an unity of a private university with communitary characteristics, and based on Balanced Scorecard (BSC), contemplating its four perspectives: financial, of its clients, of its internal processes and of learning and growing. We used a qualitative validation and converged to a quantitative methodology denominated fuzzy logic. A theoretical review, focusing the strategic management and the deeping into the system of evaluation of performance called Balanced Scorecard, was used to fundament this paper. To validate the Strategic Map (SM), we used the diffusing logic, because it enlarges the relations of linear cause and effect and contemplates the relations in which everything depends on everything. This way, we significantly help the decisory process with the identification of prioritary elements for the construction of the map. In relation to the technical procedur
Keywords: lógica difusa; mapa estratégico; mensuração; indicadores de desempenho; fuzzy logic; measurement; performance indicators; strategic map; balanced scorecard; Ciências Sociais Aplicadas